Modeling and test on height adjustment system of electrically-controlled air suspension for agricultural vehicles - Yuexia, Chen; Long, Chen; Ruochen, Wang; Xing, Xu; Yujie, Shen; Yanling, Liu (International Journal of Agricultural and Biological Engineering, 2016)
To reduce the damages of pavement, vehicle components and agricultural product during transportation, an electric control air suspension height adjustment system of agricultural transport vehicle was studied by means of simulation and bench test. For the oscillation phenomenon of vehicle height in driving process, the mathematical model of the vehicle height adjustment system was developed, and the controller of vehicle height based on single neuron adaptive PID control algorithm was designed. The control model was simulated via Matlab/Simulink, and bench test was conducted. Results show that the method is feasible and effective to solve the agricultural vehicle body height unstable phenomenon in the process of switching. Compared with other PID algorithms, the single neuron adaptive PID control in agricultural transport vehicle has shorter response time, faster response speed and more stable switching state. The stability of the designed vehicle height adjustment system and the ride comfort of agricultural transport vehicle were improved. Keywords: agricultural transport vehicle, electric control, air suspension, height adjustment system, vehicle body height, single neuron adaptive PID DOI: 10.3965/j.ijabe.20160902.1852 Citation: Chen Y X, Chen L, Wang R C, Xu X, Shen Y J, Liu Y L. Modeling and test on height adjustment system of electrically-controlled air suspension for agricultural vehicles. Int J Agric & Biol Eng, 2016; 9(2): 40－47.